The Role of Radiotherapy in the Treatment of Lung Cancer: A Review of Therapeutic Methods and Effects - Komada, Dawid; Doman, Katarzyna; Najdek , Agnieszka; Hermanowicz , Kamil; Oleksy , Daria; Kaczmarska , Urszula; Mycyk , Marcin; Cioch, Michał Jakub; Woźniak , Aleksandra; Nowak , Julia (Journal of Education, Health and Sport, 2025)
Introduction Lung cancer is a leading cause of cancer-related deaths worldwide, with rising cases and mortality. In 2022, there were 2.48 million new cases and 1.8 million deaths globally. The primary risk factor is tobacco smoking, though genetic factors, pollution, and other exposures also contribute. Lung cancer is divided into Non-Small Cell Lung Cancer (NSCLC), which includes adenocarcinoma, squamous cell carcinoma, large-cell carcinoma; and Small Cell Lung Cancer (SCLC), characterized by rapid growth, early metastatic spread and greater chemosensitivity in comparison to NSCLC. Treatment depends on the cancer type and stage, with surgery and radiotherapy being treatment of choice for NSCLC and chemoradiotherapy for SCLC. Materials and methods This article is the result of the review of the scientific literature available in PubMed database using keywords: “Lung Cancer”, “Radiotherapy”, “Non-Small Cell Lung Cancer”; “Small Cell Lung Cancer” Aim of study The aim of the study is to summarize available knowledge about various methods of treatment of lung cancer by means of radiation therapy and its diverse techniques. The epidemiology, etiology, staging and methods of treatment were summarized and described. Modern radiotherapy techniques for treating lung cancer have also been included. Conclusions For NSCLC, modern techniques like stereotactic radiotherapy (SBRT/SABR) provide surgical-level effectiveness in early stages with reduced toxicity, while concurrent chemoradiotherapy is optimal for inoperable stage III disease. Palliative radiotherapy remains vital for symptom relief in advanced stages. For SCLC, concurrent chemoradiotherapy is the standard for limited-stage disease, while prophylactic cranial irradiation (PCI) and thoracic radiotherapy improve survival in extensive-stage cases responding to chemotherapy.